2015
DOI: 10.12816/0012176
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Effects of Infestation with Pediculosis Capitis and Scabies among Primary School Students in Cairo , Egypt

Abstract: Background: Pediculosis capitis (PC) and scabies are an important public health problem in childhood. They have a worldwide distribution. Also, they have many effects on the infested students. Objectives: To define the prevalence of PC and scabies, to find out the socio-demographic, environment, and health care behavior risk factors, and to determine the effects on the studied students in Cairo, Egypt. Subjects and Methods: A cross-section, analytical study design was chosen to conduct this work. Three primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Women with parity of one may be related to the young age of pregnant women, and young women have a higher risk of pre-eclampsia. 6 Our finding is consistent with a study conducted at Soeselo Tegal District General Hospital in Central Java. 14 In addition, a case control study in Cairo also documented that parity is a risk factor of pre-eclampsia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Women with parity of one may be related to the young age of pregnant women, and young women have a higher risk of pre-eclampsia. 6 Our finding is consistent with a study conducted at Soeselo Tegal District General Hospital in Central Java. 14 In addition, a case control study in Cairo also documented that parity is a risk factor of pre-eclampsia.…”
Section: Discussionsupporting
confidence: 92%
“…14 In addition, a case control study in Cairo also documented that parity is a risk factor of pre-eclampsia. 6 However, other study conducted at Padang District General Hospital, West Sumatra Province, found that parity of 1 or >3 was not associated with pre-eclampsia. 15 Similar finding was also reported by a study in Tangerang, Banten which revealed that there was no association between parity and pre-eclampsia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A similar finding was reported in Cote d'Ivoire [15]. In contrast, El-Moselhy et al [13] in Egypt and Lulu et al [12] in Ethiopia both found that skin diseases were significantly more common in females than males in their studies. Other authors however reported that gender of participants had no association with the occurrence of skin diseases [11,12].…”
Section: Discussionsupporting
confidence: 77%
“…A study done among primary school children in Egypt [13] reported sociodemographic factors associated with a higher prevalence of skin diseases to include attendance of public school; low parental education, occupation and social status. Personal hygiene risk factors for skindiseases were poor body, hair and environmental hygiene while health care behaviour risk factors were lack of skin examination for students, no early consultation for skin diseases and failure to comply with prescribed therapy.…”
Section: Introductionmentioning
confidence: 99%